2019
DOI: 10.1037/vio0000210
|View full text |Cite
|
Sign up to set email alerts
|

Examining within-person and between-person associations of family violence and peer deviance on bullying perpetration among middle school students.

Abstract: These findings provide a more nuanced lens from which to view the co-occurring relations between family and peer ecologies. Prevention and intervention efforts should target peer relations to reduce the effect of family violence on bullying behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
5
0
2
Order By: Relevance
“…For the second part in our mediation model (i.e., deviant peer affiliation → bullying perpetration), we found that deviant peer affiliation was significantly positively associated with bullying perpetration. This finding is in line with the social development model (Farrington et al, 2018), as well as the previous research indicating that adolescents with higher levels of deviant peer affiliation display more bullying perpetration (Grant et al, 2019; Hong et al, 2017; Wang et al, 2020). That is, peers can particularly affect adolescents’ development and behavior socialization.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For the second part in our mediation model (i.e., deviant peer affiliation → bullying perpetration), we found that deviant peer affiliation was significantly positively associated with bullying perpetration. This finding is in line with the social development model (Farrington et al, 2018), as well as the previous research indicating that adolescents with higher levels of deviant peer affiliation display more bullying perpetration (Grant et al, 2019; Hong et al, 2017; Wang et al, 2020). That is, peers can particularly affect adolescents’ development and behavior socialization.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this notion, many empirical studies have found that deviant peer affiliation significantly predicts adolescents’ problem behavior (Cutrín et al, 2019; Hinnant et al, 2016; Zhu et al, 2016;). Numerous cross-sectional studies have found that adolescents who affiliate with deviant peers are more likely to bully others (Grant et al, 2019; Lin et al, 2018; Tian et al, 2019; Wang et al, 2020). Furthermore, two longitudinal studies further confirm that deviant peer affiliation significantly predicts adolescents’ bullying perpetration (Cho et al, 2017; Hong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have linked family violence and witnessing intimate partner violence (IPV) with concurrent bullying perpetration in children (Grant, Merrin, King, & Espelage, 2018;Baldry, 2003;Voisin & Hong, 2012). A study of 1,050 children in South Africa found that witnessing IPV was a primary risk factor for aggressive behavior and bullying peers, even after controlling for factors such as food insecurity and orphanhood status (Cluver, Bowes, & Gardner, 2010).…”
Section: Home Environmentmentioning
confidence: 99%
“…In addition to the personal characteristics, such as gender, personality traits, low self‐control, and empathy, studies have also identified contextual factors such as exposure to parental violence, family conflict, prior involvement in bullying, and having friends who bully others or engage in delinquent and antisocial tendencies have been shown to increase the risk of engaging in school bullying perpetration (Álvarez‐García et al., 2015 ; Grant et al., 2019 ; Hemphill et al., 2012 ; Holt et al., 2009 ; Lebrun‐Harris et al., 2019 ). For instance, a recent longitudinal study consisting of a sample of 1,194 5th, 6th, and 7th‐grade students in U.S. middle schools found a positive main effect for both family violence and peer deviance on levels of school bullying perpetration (Grant et al., 2019 ). Other studies have also found that parental violent behavior is a significant predictor of SV or TDV (e.g., Davis et al., 2020 ; Giordano et al., 2015 ), so this study is limited to this form of parenting, although other parenting styles would certainly be important to analyze as well.…”
Section: Introductionmentioning
confidence: 99%